Consumer preference for genetically modified (GM) food: the case of less saturated fat palm oil in Malaysia - Amin, Latifah; Othman, Jamal; Goh, Hong Lip; Jusoff, Kamaruzaman (Academic Journals, 2011)
Identification of consumer preference for genetically modified (GM) food is a complex process, as the consumer’s decision may differ based on information received. The aim of this study is to capture the determinants of consumer preference for GM palm oil that has less saturated fat using discriminant analysis and binary logistic regression. Data was collected via a face to face survey of 1017 respondents within the affluent Klang Valley area, near Kuala Lumpur. Results from both models indicate that consumer preference is mainly shaped by perception variables such as health effect, religious views and socio-demographic variables like younger age and middle level income. Besides, respondents who were more optimistic and knowledgeable of biotechnology also tend to favor GM palm oil. The study further found that most respondents (56%) were undecided or unwilling to purchase GM food. Overall, results imply the importance of credible and effective dissemination of consumer information by the relevant authorities in the country.